THE EFFECTIVENESS OF THE USE OF ENGLISH POP SONGS IN TEACHING VOCABULARY IN SMP - Imliyana, .; ., Suhartono; Husin, Syarif (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract : Vocabulary are needed to expand the students’ capability to understand about new ideas. Lack of vocabulary definitely makes the process of communication difficult. The purpose of this research is to investigate whether or not the use of English pop songs is effective in teaching vocabulary to the eighth grade students of SMPN 16 Pontianak. In this research, writer employs the measurement technique to measure the students’ vocabulary. The calculation of students, score by using t-test is 11.83. And based on t-value, it is higher than t-table 34 df (degree of freedom) that is 2.04 in the level 0.05. The result of the computation of the significant of the treatment is 2.01.It is higher than 0.8 and based on the crtiteria of effectiveness, it is categorized as high or effective research finding. In the other words, the English Pop Songs in an effective media to teach vocabulary. It can increase the students’ vocabulary mastery significantly.   Abstrak : Kosakata dibutuhkan untuk mengembangkan kemampuan siswa dalam memahami ide-ide baru. Tujuan dari penelitian ini adalah untuk meneliti apakah benar atau tidak penggunaan dari lagu-lagu pop Bahasa Inggris efektif dalam mengajarkan kosakata Bahasa Inggris kepada siswa kelas delapan SMPN 16 Pontianak. Dalam penelitian ini, penulis menerapkan teknik pengukuran untuk mengukur penguasaan kosakata siswa. Penghitungan dari nilai siswa menggunakan t-test adalah 11,83. Dan berdasarkan pada nilai t, lebih tinggi dari pada t-table 34 df (degree of freedom) yaitu 2,04 pada tingkat 0,05. Hasil dari penghitungan pasti pada pengajaran siswa adalah 2,01. Hal tersebut lebih tinggi dari 0,8 dan berdasarkan padar kriteria dari keefektifan, hal tersebut dikategorikan sebagai lebih tinggi atau hasil penelitian tersebut efektif. Dengan kata lain, lagu-lagu pop Bahasa Inggris adalah media yang efektif dalam mengajar kosakata Bahasa Inggris secara berarti.